Soft and elastic hydrogel-based microelectronics for localized low-voltage neuromodulation - Liu, Yuxin; Liu, Jia; Chen, Shucheng; Lei, Ting; Kim, Yeongin; Niu, Simiao; Wang, Huiliang; Wang, Xiao; Foudeh, Amir M.; Tok, Jeffrey B.-H.; Bao, Zhenan (Nature biomedical engineering, 2019)
Narrowing the mechanical mismatch between tissue and implantable microelectronics is essential for reducing immune responses and for accommodating body movement. However, the design of implantable soft electronics (on the order of 10 kPa in modulus) remains a challenge because of the limited availability of suitable electronic materials. Here, we report electrically conductive hydrogel-based elastic microelectronics with Young’s modulus values in the kilopascal range. The system consists of a highly conductive soft hydrogel as a conductor and an elastic fluorinated photoresist as the passivation insulation layer. Owing to the high volumetric capacitance and the passivation layer of the hydrogel, electrode arrays of the thin-film hydrogel ‘elastronics’, 20 μm in feature size, show a significantly reduced interfacial impedance with tissue, a current-injection density that is ~30 times higher than that of platinum electrodes, and stable electrical performance under strain. We demonstrate the use of the soft elastronic arrays for localized low-voltage electrical stimulation of the sciatic nerve in live mice. Conductive and elastic hydrogel-based microelectronic arrays with high current-injection density and low interfacial impedance with tissue enable the localized low-voltage electrical stimulation of the sciatic nerve in live mice.